Description of the karyotypes of Stejneger's beaked whale (Mesoplodon stejnegeri) and Hubbs’ beaked whale (M. carlhubbsi) - Kurihara,Nozomi (2017)
Abstract The genus Mesoplodon (Cetacea: Odontoceti: Ziphiidae) is one of the few cetacean genera with the karyotype 2n = 42. The 2n = 42 karyotype of M. europaeus and M. carlhubbsi is largely consistent with the general cetacean karyotype 2n = 44, although other 2n = 42 karyotypes do not exhibit clear homologies with the general cetacean karyotype. Therefore, the chromosomes of Mesoplodon species may be the key to understanding cetacean karyological evolution. In the present study, the male karyotypes of M. stejnegeri and M. carlhubbsi were examined. In both species, the diploid number of the male karyotype was 42. Both species had the following characteristics: 1) a huge subtelocentric X chromosome with a large C-block; 2) a small metacentric Y chromosome; 3) nucleolus organizer regions (NORs) in the terminal regions of a large autosome and one or two small metacentric autosomes; 4) small metacentric autosomes; 5) large submetacentric and subtelocentric autosomes; 6) less accumulated C-heterochromatin in the centromeric region; and 7) heteromorphism in C-heterochromatin accumulation between homologues. Characteristics 1 and 3 are peculiar to only the karyotypes of Mesoplodon species, whereas characteristics 4, 5, 6, and 7 are also found in the species with the general cetacean karyotype 2n = 44.